The impact of food safety scandals on pork prices from consumer concern perspective: evidence from China - Wan, Wenyu; Tao, Jianping (Frontiers in Sustainable Food Systems, 2023)
In the era of fast communication, consumer attention is a hidden demand signal that cannot be ignored. This study investigates the impacts of media coverages on pork prices from the perspective of consumer concerns. We employ monthly panel data spanning from January 2018 to June 2021 at the provincial level. Specifically, the study investigates the mediating role of consumer attention, which is categorized into “active attention” and “passive attention,” in the relationship between food scandal report and pork prices. The empirical results suggest a negative short-term correlation between food scandals coverages and pork prices, and reveal that passive-guided consumer attention plays a more significant mediating role than active attention in this relationship. Furthermore, a heterogeneity analysis based on the North–South partition indicates that the mediating transmission effect of consumer attention is more pronounced in regions with relatively stable supply. Overall, this study contributes to the existing theoretical literature on the impact of media coverages on agricultural prices, and provides practical implications for the government to regulate media coverages, and guide consumers to respond appropriately to food safety risks.